INOVASI PEMASARAN MELALUI MEDIA SOSIAL: KAJIAN LITERATUR - Loso Judijanto; Fauziah Nur Hutauruk (ADISAM PUBLISHER, 2025)
This literature review explores the role of marketing innovation through social media in enhancing interaction between companies and consumers. Social media has proven to be a powerful platform for increasing customer engagement, developing brand awareness, and promoting products in a personalised and interactive manner. By leveraging social media analytics, companies can collect real-time consumer behaviour data and adjust marketing strategies according to dynamic market needs. However, challenges such as maintaining a balance between personalisation and privacy, managing consistent and relevant content, and adapting to changes in social media algorithms and technology are the main focus. The study concludes that while marketing innovation through social media oflers great opportunities for business growth, its success requires in-depth understanding and a well-planned strategy